2020
DOI: 10.2147/idr.s273759
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomonas aeruginosa Type III Secretion System Virulotypes and Their Association with Clinical Features of Cystic Fibrosis Patients

Abstract: Purpose Pseudomonas aeruginosa appears as the main pathogen in cystic fibrosis (CF) involved in recurrent pneumonia and pulmonary exacerbations. The type III secretion system (T3SS) is one of its main determinants of virulence and is associated with poor clinical progression and increased mortality. This study determined the relationship of clinical features of patients with CF and P. aeruginosa T3SS virulotypes. Materials and Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…ExoS, whose production was recently associated with chronic infections and worse clinical outcomes in CF patients [ 128 ] is found in 58–72% of the clinical isolates [ 113 ] and possesses the same bifunctional activity as ExoT [ 117 ]. Its GAP activity is directed towards the same three GTPases, but unlike ExoT, the ADPRT domain of ExoS targets a wide range of cell factors and pathways, thereby producing several adverse effects on the host cells, such as cell death, actin cytoskeletal disruption, inhibition of DNA synthesis, vesicular trafficking, or endocytosis [ 117 ].…”
Section: Pseudomonas Aeruginosa Virulence Factomentioning
confidence: 99%
“…ExoS, whose production was recently associated with chronic infections and worse clinical outcomes in CF patients [ 128 ] is found in 58–72% of the clinical isolates [ 113 ] and possesses the same bifunctional activity as ExoT [ 117 ]. Its GAP activity is directed towards the same three GTPases, but unlike ExoT, the ADPRT domain of ExoS targets a wide range of cell factors and pathways, thereby producing several adverse effects on the host cells, such as cell death, actin cytoskeletal disruption, inhibition of DNA synthesis, vesicular trafficking, or endocytosis [ 117 ].…”
Section: Pseudomonas Aeruginosa Virulence Factomentioning
confidence: 99%
“…In connection with this, CF isolates from chronic infection strains often lacks the PAPI-2 encoded cytotoxin ExoU. They instead harbour the type III secretion system (T3SS) effector ExoS, which is chromosomally encoded and has less virulent properties than ExoU [142][143][144][145]. However, mutations in major virulence and quorum-sensing (QS) regulators, such as retS, exsA or lasR, are the main perpetrators of the lowvirulence state of chronic P. aeruginosa (Fig.…”
Section: Virulencementioning
confidence: 99%
“…Pseudomonas aeruginosa is known to have five TSSs, of which Types I (T1SS), II (T2SS), and III (T3SS) are involved in the virulence of this pathogen. Several studies have linked these TSSs with poor outcomes of patients with acute respiratory diseases (i.e., pneumonia), with T3SS being one of the most clinically relevant virulence determinants (Hauser, 2011;McMackin et al, 2019;Sarges et al, 2020). In this context, we detected ExoTSY exotoxins-encoding genes in both clinical and environmental strains.…”
Section: Discussionmentioning
confidence: 88%
“…In this context, we detected ExoTSY exotoxins-encoding genes in both clinical and environmental strains. ExoTSY exotoxins are secreted by T3SS and reported to be involved in lung injury, pulmonaryvascular barrier disruption, and end-organ dysfunction in chronic infections, mainly in CF patients; as well as with mortality in animal models (Lu et al, 2014;Sarges et al, 2020;Jurado-Martín et al, 2021). Interestingly, the toxA gene (exotoxin A), which is present in the most clinically P. aeruginosa strains (Khosravi et al, 2016) was also identified in environmental strains.…”
Section: Discussionmentioning
confidence: 99%